Floral differentiation in arabica coffee (Coffea arabica L.) under different levels of radiation - Queiroz-Voltan, Rachel Benetti; Fahl, Joel Irineu; Carelli, Maria Luíza Carvalho (Coffee Science - ISSN 1984-3909, 2011)
Little is known about the radiation effect on the induction and differentiation phases of reproductive nodes of Coffea arabica L. This knowledge would allow defining shading levels, or planting densities, appropriate to maximize the development, the production and the sustainability of the coffee crop. Floral differentiation was evaluated in plants of ‘Catuai Vermelho IAC 81, cultivated under four radiation regimes (30, 50, 70 and 100%), by using different plastic screens. Plagiotropic branches with fruits were collected from february to september, for two consecutive years. Slides of longitudinal sections of the node regions were mounted for the characterization and quantification of histological stages of bud differentiation. The undifferentiated buds formation began in February and, their differentiation to reproductive buds, in April/May. At the end of July practically all buds were already reproducing. The percentage of undifferentiated buds in February was 50% lower in 2005 because the sample branches had a large number of fruits in the basal region, indicating that the branches in a year of high production show a delay in flower bud differentiation in relation to the branches with few fruits during low productive years. The intermediate levels of shading, 50 to 70%, solar radiation, anticipated the development of buds from the plants grown under full sun in years of high production, the opposite occurred in the low productive years. The percentage of undifferentiated buds between irradiance treatments varied more than the percentage of reproductive buds, indicating that the radiation intensity has a greater effect in the early stages of floral differentiation.